Comparison in terms of delays in the construction contracts used in Turkey - Özkaptan Alptekin, Gamze (Croatian Soc Civil Engineers-Hsgi, Berislaviceva 6, Zagreb, 00000, Croatia, 2017)
Developing countries offer a market opportunity for construction industry. Turkish construction market is one of the attractive ones, after Russia in the Middle East, because of quantitative and qualitative needs with regard to both structural and infrastructural projects. General Conditions of Construction Contracts (GCCC) are commonly used for public procurements in Turkey, while FIDIC Conditions of Contract for Construction are used less often. In this paper, GCCC is compared with FIDIC Conditions of Contract for Construction 1999, in terms of delays, in order to provide guidance to potential contractors.
Keywords: construction contracts; conditions of contracts; delay; FIDIC; public procurement; public procurement laws; Projects